2018
DOI: 10.3390/ht7030026
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Identification of Related Proteins in the Immune System of the Crayfish Procambarus clarkii

Abstract: The freshwater crayfish Procambarus clarkii is an animal model employed for physiological and immunological studies and is also of great economic importance in aquaculture. Although it is a species of easy husbandry, a high percentage of its production is lost annually as a result of infectious diseases. Currently, genetic information about the immune system of crustaceans is limited. Therefore, we used the abdominal nerve cord from P. clarkii to obtain its transcriptome using Next Generation Sequencing (NGS) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…The immune response of crayfish is primarily generated from the immunocompetent cells and mucus of intestinal mucosal membrane (Lieschke & Trede, 2009; Ángeles Esteban, 2012). Among the factors, IL, interferon, TNF are the major cytokine candidates associated with immunity and inflammation of crayfish (Goins, 2003; Araki et al, 2004; Jiang et al, 2015b; Calderón-Rosete et al, 2018). The present study revealed significant ( P < 0.05) up-regulation of pro-inflammatory cytokine genes (IL-1β, IL-17F, and TNF-α) in BSF supplemented diet groups while similar expression patterns were observed for FM and PBM fed groups.…”
Section: Discussionmentioning
confidence: 99%
“…The immune response of crayfish is primarily generated from the immunocompetent cells and mucus of intestinal mucosal membrane (Lieschke & Trede, 2009; Ángeles Esteban, 2012). Among the factors, IL, interferon, TNF are the major cytokine candidates associated with immunity and inflammation of crayfish (Goins, 2003; Araki et al, 2004; Jiang et al, 2015b; Calderón-Rosete et al, 2018). The present study revealed significant ( P < 0.05) up-regulation of pro-inflammatory cytokine genes (IL-1β, IL-17F, and TNF-α) in BSF supplemented diet groups while similar expression patterns were observed for FM and PBM fed groups.…”
Section: Discussionmentioning
confidence: 99%
“…Genomic research on non-model organisms is faced by the challenge of annotating large sets of genes from unknown origin. This challenge is particularly evident in Crustaceans [47,48], which are still largely underrepresented in genomic studies. To date, only 48 out of 727 genome assemblies representing Pancrustacea belong to Crustaceans (with the remaining 679 genomes belonging to Hexapoda) (Genomes-NCBI Datasets, accessed: April 2021).…”
Section: Innate Immunity Transcriptsmentioning
confidence: 99%
“…With the rapid development of the aquaculture industry, P. clarkii is often infected by various pathogens such as bacteria, viruses, and spiroplasmas [26][27][28][29], resulting in severe decreases in P. clarkii production. Therefore, significant anti-microbial research and studies of the immune response of P. clarkii have been performed, especially using transcriptome analysis by next-generation sequencing (NGS) [29][30][31][32]. NGS is a high-throughput sequencing technology and constitutes a variety of strategies that depend on a combination of template preparation, sequencing and imaging, and genome alignment and assembly methods [33,34].…”
Section: Introductionmentioning
confidence: 99%
“…Combined with the de novo assembly methods such as Trinity, the full-length transcriptome assembly from NGS data can be implemented without a reference genome and does not require the correct alignment of reads to known splice sites [35,36]. Currently, NGS is frequently used to analyze the transcriptome variation of P. clarkii in a variety of research areas, including pathogen infection as mentioned above [26][27][28][29], the immune system [31,37], neurohormone regulation [38], and gonadal development [37,39].The NGS transcriptomic analysis of P. clarkii revealed that the ovary and testis, the major reproductive organs, were more closely related to the pathways of DNA replication, cell cycle, and meiosisyeast compared to other non-reproductive organs (e.g., hepatopancreas and muscle) [37]. In addition, using 454 pyrosequencing technology, a differential expression analysis between the sexually mature ovary and testis of P. clarkii was performed, and the results identified gonadal development related genes that were highly expressed in ovary and testis [39].…”
Section: Introductionmentioning
confidence: 99%